2004
DOI: 10.1253/circj.68.938
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation to Low-Intensity Exercise on a Cycle Ergometer by Patients With Acute Myocardial Infarction Undergoing Phase I Cardiac Rehabilitation

Abstract: BackgroundThe adaptation of patients with acute myocardial infarction (AMI) to a phase I rehabilitation program has not been widely assessed. Methods and Results Forty-two male patients (62±8 years) with AMI were classified as exercise tolerant (group A, n=25) or excessive response (systolic blood pressure (SBP) increase >30 mmHg during exercise; group B, n=17). Hemodynamic parameters during exercise using a cycle-ergometer were monitored for the first 3 days. The power of low-and high-frequency components (LF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0
3

Year Published

2005
2005
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 43 publications
1
5
0
3
Order By: Relevance
“…The results of the present study demonstrate that a physiotherapy session composed of early postural change, orthostatism, deep breathing and walking is feasible and safe during hospitalisation in patients diagnosed with decompensated CHF [24]. In addition, despite the absence of HRV changes during postural changes and reduced HRV during walking and recovery compared with matched controls, deep breathing exercises and walking positively influenced HRV in these patients.…”
Section: Discussionsupporting
confidence: 48%
“…The results of the present study demonstrate that a physiotherapy session composed of early postural change, orthostatism, deep breathing and walking is feasible and safe during hospitalisation in patients diagnosed with decompensated CHF [24]. In addition, despite the absence of HRV changes during postural changes and reduced HRV during walking and recovery compared with matched controls, deep breathing exercises and walking positively influenced HRV in these patients.…”
Section: Discussionsupporting
confidence: 48%
“…It reports a HR increase in patients with AMI during an aerobic exercise on a cycle ergometer; on the basis of a reduction in HF component during exercise,33 the authors conclude that it is due to a decrease of the parasympathetic activity.…”
Section: Discussionmentioning
confidence: 95%
“…3,5 Psychological and educational interventions have additional effects and can lead to changes in risk factors, in the patient's life style, and social and psychological function- ing. 1,2,7,[33][34][35][36][37][38] Many published studies have shown an increase in health-related QOL in patients with CHD who undergo CR. 1,3,[5][6][7][8][9][10][11]22,[39][40][41] More profound changes have been observed in patients who participate in comprehensive CR programs based on physical activity as well as psychological and educational approaches, compared with patients who have only physical training.…”
Section: Discussionmentioning
confidence: 99%